A Cost-Benefit Analysis of A Community Free Clinic. Issue 2 (3rd April 2019) - Stillmank, Erin; Bloesl, Katie; McArthur, Erin; Artz, Benjamin; Lancaster, Rachelle J.
ABSTRACT: Uninsured patients lacking access to primary and preventive care continues to be an issue. The purpose of this analysis is to describe operating costs surrounding a nurse-driven freestanding community clinic and to calculate quality of life benefits using clinically preventable burden scores. A retrospective records review of patients ( n = 200) receiving care at a free clinic were used. Annual costs were $387, 252. The benefit gained in quality-adjusted life years is estimated to be 57.47–203.94 yielding a return on investment ranging from $1, 200, 264-$8, 948, 184. Free clinics have sustained cost savings over time. Policies addressing this form of care are imperative.